Kurang Efektivitasnya Pernikahan Di Masa Pandemi Covid-19 Di Kec. Medan Helvetia Sumatra Utara Indonesia - Mahendra, Yusril; Ananda, Amin; Meli Utami Paner; Nurul Ulfa (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
In Indonesia, the COVID-19 pandemic has resulted in the paralysis of community activities both in terms of economic, social and even religious activities. For example, in terms of marriage, the government implements the PSBB (Large Scale Restriction) policy, where people who want to carry out wedding activities are limited by the Office of Religious Affairs (KUA) on the basis of rules from the government to suppress Covid-19 cases in Kec. Medan Helvetia, North Sumatra, Indonesia. Thus this study intends to investigate how the effectiveness of marriage during the Covid-19 pandemic in the district. Medan Helvetia North Sumatra Indonesia, we conducted a survey in the city of Medan Helvetia North Sumatra, Indonesia. By using qualitative research methods, we can find out firsthand that basically Marriage in the Covid-19 Pandemic Period is not very effective and causes many difficulties from various parties. From the results of the study, it is expected that all people who want to carry out wedding activities to know and understand the procedures for marriage require several stages with procedures that have been set by the Office of Religious Affairs (KUA). Keywords: marriage, Covid-19, Effectiveness, Indonesian society,